The inhibition of Streptococcus mutans glucosyltransferase enzyme activity by mangosteen pericarp extract - Nirawati Pribadi; Yovita Yonas; Widya Saraswati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Streptococcus mutans (S. mutans) is a bacterium that plays an important role in the pathogenesis of dental caries. Streptococcus mutans produces the glucosyltransferase enzyme which is capable of catalyzing glucan synthesis in the progression of dental caries. Certain treatments involving traditional plant use have been developed to eradicate Streptococcus mutans as a means of preventing the formation of dental caries. One of these is mangosteen pericarp extract containing a number of polyphenols that have the capacity to act as antibacterial agents, namely; tannin, mangostin, and flavonoid. Purpose: The research aimed to investigate the inhibitory power of mangosteen pericarp extract against Streptococcus mutans producing the glucosyltransferase enzyme. Methods: The research used mangosteen pericarp extract at concentrations of 0.39% and 0.78% as the treatments, while 0.12% chlorhexidine gluconate was used as a positive control, and distilled water as a negative control. Each group consisted of six samples. Mangosteen peels extracted with 96% ethanol (maceration method) and mangosteen extract constituted 5% of the total weight of the mangosteen pericarp. Supernatant containing Gtf enzyme produced from a culture medium and centrifuged at 1500 rpm for 10 minutes at 4o C. Glucosyltransferase enzyme activity was measured by analyzing the extensive fructose area by means of High Performance Liquid Chromatography (HPLC). The extensive fructose area was determined according to time retention in each group. Results: Mangosteen peel extract at concentrations of 0.39% and 0.78% demonstrated greater ability than the negative control group (sterile aquades) and similar ability to the positive group (chlorhexidine 0.12%) to inhibit the activity of the Gtf enzyme or S. mutans bacteria. Conclusion: Mangosteen pericarp extract has the ability to inhibit the activity of Streptococcus mutans in producing glucosyltransferase enzyme.